Nutri-Score labelling system – selected legal aspects - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2024)
The subject under consideration is the voluntary Nutri-Score labelling system called FOP (front-of-pack) which is an increasingly common method of labelling the nutritional value on the front of the packaging of food products. While it has found recognition in many EU Member States, its use continues to provoke much controversy and doubt. The Nutri-Score system is used quite extensively not only in Poland, but also throughout the EU. Many Member States have regulated its use by law. The aim of this paper is to evaluate the Nutri-Score system and to determine whether it meets the requirements of food law in terms of labelling foodstuffs and, in particular, whether it is likely to mislead consumers. In the author’s opinion, constant modification and updating of the system that has been going on has already allowed for at least some elimination of the earlier reservations. It is also recommended to adapt the Nutri-Score system to the requirements of food law, to develop a modified FOP labelling systems, or consider a development of a completely new solution. However, simplifying the nutritional assessment of food products to a single symbol so that it is clear, not misleading, and respects the generally applicable requirements of food law is extremely difficult to do.